ALT in Preeclampsia - Sultana, Razia; Ahmed, Selina; Sultana, Nasima; Diba, Farah (Delta Medical College Journal, 2024)
Background: Preeclampsia is the most frequent cause of abnormal liver function test in pregnancy. Women with preeclampsia and raised serum alanine aminotransferase (ALT) have chance of greater proteinuria and more maternal complications than those with normal liver function. Objective: The present study was designed to assess the association of serum ALT with preeclampsia. Materials and method: A case control study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka, Bangladesh, from July 2010 to June 2011. From the pregnant women in third trimester of pregnancy attending in Obstetrics and Gynecology Department of Dhaka Medical College Hospital, 50 diagnosed cases of preeclampsia were selected purposively as cases and 50 normal healthy pregnant women as controls. Serum ALT concentration was measured in all the study subjects. Results: The mean serum ALT concentration in cases and controls were 57.92±20.99 U/L and 15.46±2.66 U/L respectively. The level was significantly higher in cases than that of controls (p=0.001). Conclusion: The study revealed that increased serum ALT concentration is associated with preeclampsia. Delta Med Col J. Jan 2021;9(2): 65-68